Study of Financial Management Behavior Based on Financial Self-Efficacy and Financial Literacy in Small-Scale Agribusiness Development - Fithriah Napu; Dedy Takdir Syaifuddin (Journal of Global Innovations in Agricultural Sciences)
Farmers are important actors in agribusiness development. Farmers' businesses are generally classified as small businesses. Various theoretical evidence is sufficient to explain the important role of farmers in agribusiness development which is limited by financial literacy, and financial self-efficacy that influences financial management behavior. However, research on the role of financial literacy and financial self-efficacy on financial management behavior in terms of agribusiness development has not been conducted. This study aims to present new evidence on the role of financial literacy, and financial self-efficacy on financial management behavior in small-scale agribusiness. This study uses a positivist approach also known as quantitative research. Using an explanatory research design and involving around 68 small-scale agribusiness actors in Kendari City. Data were obtained through questionnaires. Data were analyzed using SEM-PLS. It was found that financial literacy by small-scale agribusiness actors can play a role in shaping financial management behavior and financial self-efficacy. Furthermore, the financial self-efficacy skills of small-scale agribusiness actors also play a role in shaping financial management behavior. The theoretical implication is that improving financial management behavior and financial self-efficacy of agribusiness actors can be done by improving financial literacy skills. Likewise, efforts to improve the financial management behavior of agribusiness actors must be supported by financial self-efficacy skills. With this approach, theoretically, agribusiness businesses can develop and be free from all financial risks that lead to business failure. Practical implications for agribusiness actors to improve financial literacy skills to be able to create and/or form financial management behavior and self-efficacy. The second concern is financial self-efficacy which needs to be pursued because it supports financial management behavior in developing agribusiness businesses. For the government, it is better to prepare regulations and instruments that support the creation of an agribusiness business climate. By considering the results of research, policies, and regulations leading to an ecosystem for the formation of financial literacy, financial self-efficacy, and financial management behavior. The research findings open up new avenues for future researchers, namely conducting further analysis using empirical data by measuring agribusiness performance based on the development of the financial curve (profit or gain). Then, it is recommended to use a qualitative paradigm, or a mixed research approach so that the research findings are more comprehensive. Keywords: Agribusiness, small business, financial literacy, financial self-efficacy, financial management behavior.